COMPARATIVE CHARACTERISTICS OF THE NUTRITIONAL VALUE OF BIG CARP, CATFISH, CARP AND PIECE CAVIAR - Z. M. Arabova; O. I. Konnova; I. Yu. Aleksanyan; A. H.-H. Nugmanov; M. S. Arabov; N. P. Memedeikina; E. V. Sokolova (Современная наука и инновации)
The study and analysis of the chemical composition and biochemical parameters of caviar raw materials of freshwater fish living in the lower reaches of the Volga confirm the fact that caviar raw materials have a relatively high energy and biological efficiency of functioning and the value of protein and lipid complexes. The biological value of protein complexes is due to the presence of the entire list of essential amino acids, the total proportion of which is higher compared to the ideal protein substance. Freshwater, like marine caviar, is an excellent source of lipids, including phospholipids, which contain a significant amount of long-chain polyunsaturated fatty acids. Therefore, in recent studies related to fish raw materials and related products, much attention is paid to them. This article provides an overview of the chemical composition and properties of caviar of four species of fish, the caviar component of which is in low demand in native and processed form in the domestic fish products market.